2015
DOI: 10.1007/s00347-014-3160-7
|View full text |Cite
|
Sign up to set email alerts
|

Trabekulektomie versus Kanaloplastik

Abstract: If a higher postoperative IOP is acceptable and additional topical glaucoma medication tolerable, canaloplasty can be considered as an alternative to trabeculectomy as the incidence of complications is low and postoperative care less intensive. Canaloplasty may also be suitable for patients with high risk of bleb failure and early glaucoma with a target IOP not necessarily requiring a filtering procedure. Therefore, canaloplasty offers a treatment option for the management of open-angle glaucoma, especially in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
(16 reference statements)
1
9
0
1
Order By: Relevance
“…However, we found similar results in the qualified success rate. We believe that our results are in line with these meta-analyses since the original studies [17][18][19][20][21] considered an IOP ⩽17 mmHg as an absolute success. In this study, we were able to achieve positive results from this comparison; however, prudence is required in the interpretation of our results in the various parameters tested, given the retrospective nature of this study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, we found similar results in the qualified success rate. We believe that our results are in line with these meta-analyses since the original studies [17][18][19][20][21] considered an IOP ⩽17 mmHg as an absolute success. In this study, we were able to achieve positive results from this comparison; however, prudence is required in the interpretation of our results in the various parameters tested, given the retrospective nature of this study.…”
Section: Discussionsupporting
confidence: 87%
“…Many comparison studies shed light on this topic over the years. [17][18][19][20][21] In a benchmark study from Ayyala et al, the authors concluded that both canaloplasty and trabeculectomy achieved a significant reduction in IOP at 12 months. They reported a mean IOP reduction of 32% with canaloplasty compared to a 43% mean IOP reduction with trabeculectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Pillunat et al described a similar efficacy by comparing the implantation of the PreserFlo™ MicroShunt and the trabeculectomy concerning IOP reduction without any additional local agents [ 21 ]. The comparison of trabeculectomy to canaloplasty revealed that the trabeculectomy was able to reduce the IOP more sufficiently than the MicroShunt and with fewer additional local agents [ 16 , 22 ]. Nevertheless, Matlach et al, as well as Vastardis et al, described a lower risk of postoperative complications after canaloplasty [ 16 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Im Folgenden sollen die Vor-und Nachteile einer fistulierenden Operation (Trabekulektomie) ausführlicher diskutiert werden, da diese gegenüber allen anderen operativen Verfahren eindeutig die beste Drucksenkung aufweist. Dies konnte in mehreren Vergleichsstudien und auch in Metaanalysen evidenzbasiert nachgewiesen werden [12,13] [14][15][16][17][18][19]. Hier sollen die Bemühungen der Moorfields-Gruppe um Sir Peng Khaw für das "save surgery system" hervorgehoben werden.…”
Section: Wann Muss Ein Glaukompatient Operiert Werden?unclassified